2007
DOI: 10.1103/physreva.75.053809
|View full text |Cite
|
Sign up to set email alerts
|

Atom localization and center-of-mass wave-function determination via multiple simultaneous quadrature measurements

Abstract: We discuss localization and center-of-mass wave-function measurement of a quantum particle using multiple simultaneous dispersive interactions of the particle with different standing-wave fields. In particular, we consider objects with an internal structure consisting of a single ground state and several excited states. The transitions between ground and the corresponding excited states are coupled to the light fields in the dispersive limit, thus giving rise to a phase shift of the light field during the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 43 publications
0
66
0
Order By: Relevance
“…Like in standing-wave localization schemes, each ratio R corresponds to several potential positions {z i } [29]. Previous localization schemes concluded that an additional classical measurement is required to determine the true position [18,22,29]. But our running-wave approach allows us to eliminate the need for an additional classical measurement, by choosing the laser field configuration such that |ξ | 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like in standing-wave localization schemes, each ratio R corresponds to several potential positions {z i } [29]. Previous localization schemes concluded that an additional classical measurement is required to determine the true position [18,22,29]. But our running-wave approach allows us to eliminate the need for an additional classical measurement, by choosing the laser field configuration such that |ξ | 1.…”
Section: Resultsmentioning
confidence: 99%
“…A particular class of subwavelength position measurement schemes is based on the spatial intensity modulation of standing-wave driving fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Note that these schemes consider only single particles, which are well isolated from the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These OSG strategies differ from other measurement devices in quantum optics, such as quantum nondemolition [5] and homodyne techniques [6], that have been extensively explored from the 1990s until now [7]. More recently, a cross-cavity OSG has been proposed-where a beam of atoms is made to cross two orthogonal cavities-to measure the location and center-of-mass wave function of the atoms [8,9]. Although the cross-cavity OSG has not yet been implemented experimentally, the cross-cavity setup has been built to test Lorentz invariance at the 10 −17 level [10].…”
mentioning
confidence: 99%
“…1, where, before entering the cavities, the atoms are confined by a circular pinhole to a small region of space centered around the superimposed nodes of the two cavity modes. Differently from the developments in [8,9], where dispersive atom-field interactions take place, we assume the two-level atoms undergo simultaneous and resonant interactions with two identical modes, one from each cavity, thus being deflected in the plane defined by the two mutually perpendicular cavities' optical axes. An appropriate ansatz on the spatial distribution of the atoms across the pinhole enables us to derive an analytical expression for the atomic momentum distribution after the atom-field interactions.…”
mentioning
confidence: 99%